Assessing the Impact of Skilled Labor on Output Growth in South Africa: An ARDL Bound Testing Approach - Okoli, Tochukwu Timothy; Tewari, Devi Datt; N.O., Eneh George (Journal of Economics and Behavioral Studies, 2018)
Economic theory emphasized the necessity of skill acquisition and conservation as a precondition for growth. This paper investigates the extent to which skilled labor can contribute to output growth in South Africa in the long run. The theoretical framework employed was based on Hicks neutral augmented CobbDouglas production function to account for the impact of technological progress on labor and capital. Skilled labor was measured with three parameters of experience (learning-by-doing), special training and educational attainments. The methodology employed the ARDL bound testing approach and found that whereas there is no short run causality running from the independent variables to the dependent variable, there was a long run causality running from the measures of skilled labor to growth. The coefficient of the ECT was both significant and negative; therefore, the system gets adjusted towards their long run equilibrium steady state at the speed of 23 percent annually. This means that the measures of skilled labor contribute to growth in the long run to the tune of 23 percent annually. The study therefore recommends investments in human capital through education and special trainings as well as to encourage knowledge transfer through globalization and from one generation to another to conserve skills.